DEVELOPMENT OF POLYURETHANE/CLAY NANOCOMPOSITES BASED ON PALM OIL POLYOL - Ummi Habibah; A Adriana; S Sariadi; M Muhammad; Halim Zaini; Sabila Yasara SA; F Fachraniah (Jurnal Sains dan Teknologi Reaksi, 2023)
Polyurethanes (PURs) are highly adaptable polymeric substances with a variety of physical and chemical attributes. High abrasion resistance, tear strength, shock absorption, flexibility, and elasticity are just a few of the desirable qualities of PURs. Despite their generally low thermal stability, this can be enhanced by utilizing clay that has been treated. From renewable resources, polyurethane/clay nanocomposites have been created. By combining oleic acid from palm oil with glycerol, a polyol for the manufacture of polyurethane by reaction with an isocyanate was created. As a catalyst and emulsifier, dodecylbenzene sulfonic acid (DBSA) was employed. Octadodecylamine (ODA-mont) and cetyltrimethyl ammonium bromide (CTAB-mont) were used to treat the unaltered clay (kunipia-F).  The d-spacing in CTAB-mont and ODA-mont were bigger than that of the pure-mont (1.142 nm) at 1.571 nm and 1.798 nm, respectively. A pre-polymer technique was used to create polyurethane/clay nanocomposites, and the micro-domain structures of segmented PU, CTAB-mont-PU 1, 3, and 5 wt%, and ODA-mont-PU 1, 3, and 5 wt% were determined by FTIR spectra. X-ray diffraction (X-RD) was used to evaluate the nanocomposites' morphology, and the results revealed that all of the intercalated type's nanocomposites were created as a result of this effort. When the surfaces of the materials were examined using transmission electron microscopy (TEM) observation and scanning electron microscopy (SEM), these were further confirmed. Thermogravimetric analysis (TGA) was used to examine thermal stability.Pure PU begins to degrade around 200°C, which is lower than the degrading rates of CTAB-mont PU and ODA-mont PU, which occur at roughly 318°C and 330°C, respectively. Both pure polyurethane (PU) and PU/clay nanocomposites have their mechanical properties, including dynamic mechanical properties, tested. With only a 5 weight percent addition of the montmorillonite CTAB-mont PU or ODA-mont PU, respectively, the tensile strength of the nanocomposites increased by more than 214% and 267%, respectively, demonstrating the impressively positive impact of the modified organoclay on the strength and elongation at break of the nanocomposites.Keywords: Clay,Palm Oil, Polyurethane